2007
DOI: 10.1017/s014338570700017x
|View full text |Cite
|
Sign up to set email alerts
|

A pasting lemma and some applications for conservative systems

Abstract: We prove that in a compact manifold of dimension n≥2, C1+α volume-preserving diffeomorphisms that are robustly transitive in the C1-topology have a dominated splitting. Also we prove that for three-dimensional compact manifolds, an isolated robustly transitive invariant set for a divergence-free vector field cannot have a singularity. In particular, we prove that robustly transitive divergence-free vector fields in three-dimensional manifolds are Anosov. For this, we prove a ‘pasting’ lemma, which allows us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 22 publications
4
99
0
3
Order By: Relevance
“…The map f a is chosen to be C ∞ flat at 0 so that F a has a homoclinic tangency of infinite order at (0, 0). Moreover since (x, y) → (x, y 1 + f a (x 1 ), y 2 , · · · , y mu ) is volume preserving we may choose θ a be also volume preserving by the pasting Lemma of Arbieto and Matheus (see Lemma 3.9 of [4]). Also θ a is C ∞ close to the identity when f a is C ∞ close to zero.…”
Section: R (R ≥ 2) Robust Examplesmentioning
confidence: 99%
“…The map f a is chosen to be C ∞ flat at 0 so that F a has a homoclinic tangency of infinite order at (0, 0). Moreover since (x, y) → (x, y 1 + f a (x 1 ), y 2 , · · · , y mu ) is volume preserving we may choose θ a be also volume preserving by the pasting Lemma of Arbieto and Matheus (see Lemma 3.9 of [4]). Also θ a is C ∞ close to the identity when f a is C ∞ close to zero.…”
Section: R (R ≥ 2) Robust Examplesmentioning
confidence: 99%
“…Let us point out that the corresponding regularization theorem for conservative flows was obtained much earlier by Zuppa [29] in 1979. In fact, in a more recent approach of Arbieto-Matheus [1], it is shown that a result of Dacorogna-Moser [13] allows one to reduce to a local situation where the regularization of vector fields which are divergence free can be treated by convolutions. However, attempts to reduce the case of maps to the case of flows through a suspension construction have not been successful.…”
Section: Introductionmentioning
confidence: 99%
“…[8]); (2) the result in [14] are replaced by the smoothness result in [3]; (3) the perturbation lemma in [6], are interchanged by its correspondent in the volume-preserving case proved in [5, Proposition 7.4]; (4) and, finally, we should use [2, Theorem 3.6] instead of [2,Theorem 3.9].…”
Section: Volume-preserving Diffeomorphismsmentioning
confidence: 99%